2007
DOI: 10.1038/sj.tpj.6500474
|View full text |Cite
|
Sign up to set email alerts
|

Allelic variation in ApoC3, ApoA5 and LPL genes and first and second generation antipsychotic effects on serum lipids in patients with schizophrenia

Abstract: Schizophrenic patients who are treated with antipsychotics, especially second generation antipsychotics, such as clozapine and olanzapine, manifest an increase in cholesterol and triglycerides as well as other changes associated with diabetes or the metabolic syndrome. Previous studies have shown that polymorphisms in several genes that regulate lipid metabolism can influence the levels of these lipids and response to drug treatment. We have investigated in an exploratory study whether polymorphisms in the apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 38 publications
3
17
0
Order By: Relevance
“…Due to antipsychotic medications in SZ and mood stabilisers in BD, those patients have an increased risk for metabolic disturbances and altered lipid metabolism (Gibbons, Thomas, Scarr, & Dean, 2010), ultimately contributing to an increased risk for cardiovascular disease (Meyer et al, 2008). Several authors observed an association between Apo concentrations in patients receiving psychiatric medication (e.g., phenothiazines, olanzapine, risperidone) (Dean et al, 2008;Sasaki et al, 1985;Smith, Segman, Golcer-Dubner, Pavlov, & Lerer, 2008;Song et al, 2014). Therefore, we controlled for potential effects of the duration of drug treatment, the dosage of the current treatment, as well as BMI values on the protein concentrations.…”
Section: Strength and Limitationsmentioning
confidence: 99%
“…Due to antipsychotic medications in SZ and mood stabilisers in BD, those patients have an increased risk for metabolic disturbances and altered lipid metabolism (Gibbons, Thomas, Scarr, & Dean, 2010), ultimately contributing to an increased risk for cardiovascular disease (Meyer et al, 2008). Several authors observed an association between Apo concentrations in patients receiving psychiatric medication (e.g., phenothiazines, olanzapine, risperidone) (Dean et al, 2008;Sasaki et al, 1985;Smith, Segman, Golcer-Dubner, Pavlov, & Lerer, 2008;Song et al, 2014). Therefore, we controlled for potential effects of the duration of drug treatment, the dosage of the current treatment, as well as BMI values on the protein concentrations.…”
Section: Strength and Limitationsmentioning
confidence: 99%
“…152 Polymorphisms in the apolipoprotein A-V (APOA5) and C-III (APOC3) genes, but not in LEP, showed an influence on triglyceride and cholesterol levels in patients treated with clozapine or olanzapine. 74 Agranulocytosis is a serious adverse effect associated with clozapine. Some studies showed strong associations between polymorphisms in genes of the major histocompatibility complex (HLA) and the occurrence of this adverse effect.…”
Section: Studies Assessing the Adverse Effects Of Clozapinementioning
confidence: 99%
“…Polymorphisms in the synaptic plasticity protein SNAP25, were also associated with weight gain [101,177]. Polymorphisms in apolipoproteins (APOE, APO5 and APOC3) and in GNB3, with roles in signaling pathways, were associated with antipsychoticinduced metabolic syndrome [129,[178][179][180]. Proteins involved in apoptosis were found to contribute to weight gain and movement disorders.…”
Section: Other Genetic Associations With Antipsychotic Side Effectsmentioning
confidence: 99%